Wind-Induced Vibration Analysis of Overhead Working Truck - Hongqi Jiang; Shuncai Li; Xianbiao Mao (Institute of Advanced Engineering and Science, 2014)
As to the complicated characteristics of overhead working truck under effects of random dynamic wind, the traditional method is difficult to reflect its dynamic response in real time, in the study; it proposes the random wind induced vibration response analysis method based on the finite element method and pseudo-excitation method. An it regards the vibration of the fluctuating wind load as coherent random vibration under stationary random excitation, and it uses Davenport wind velocity spectrum which does not change with height, the correlation of the wind excitation are considered. It takes the folding type arm overhead working truck as example, the random wind vibration analysis are performed, and it gets the acceleration response spectrum and root mean square the of aerial work platform. The analysis results show that the low-order frequency will cause great vibration of the work platform, and the vertical one third of the root-mean-square of acceleration is below international standards, it has no uncomforted effect on operation workers.